On polynomial approximation of solutions of differential-operator equations - Orudzhev, G. D. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Polynomial approximations are constructed for the solutions of differential equations of the first and second order in a Banach space for which the Cauchy problem is stated correctly.